2020
DOI: 10.3389/fimmu.2020.607754
|View full text |Cite
|
Sign up to set email alerts
|

Gut–Liver Immune Response and Gut Microbiota Profiling Reveal the Pathogenic Mechanisms of Vibrio harveyi in Pearl Gentian Grouper (Epinephelus lanceolatus♂ × E. fuscoguttatus♀)

Abstract: Vibrio harveyi causes vibriosis in nearly 70% of grouper (Epinephelus sp.), seriously limiting grouper culture. As well as directly inhibiting pathogens, the gut microbiota plays critical roles in immune homeostasis and provides essential health benefits to its host. However, there is still little information about the variations in the immune response to V. harveyi infection and the gut microbiota of grouper. To understand the virulence mechanism of V. harveyi in the pearl gentian grouper, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 75 publications
(89 reference statements)
4
29
0
Order By: Relevance
“…The sampling of 16S sequencing analysis followed the method published in previous studies by Deng et al. ( 44 ). For the sampling of larvae, only 27 dpf larvae (n = 6) were sampled for HE staining at the meantime of imaging the adaptive immune cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling of 16S sequencing analysis followed the method published in previous studies by Deng et al. ( 44 ). For the sampling of larvae, only 27 dpf larvae (n = 6) were sampled for HE staining at the meantime of imaging the adaptive immune cells.…”
Section: Methodsmentioning
confidence: 99%
“…For all omics studies, the hindgut from one female and one male adult zebrafish were mixed for each sample (three repetitions) to avoid sex-biased differences for both transcriptome and 16S. The sampling of 16S sequencing analysis followed the method published in previous studies by Deng et al (44). For the sampling of larvae, only 27 dpf larvae (n = 6) were sampled for HE staining at the meantime of imaging the adaptive immune cells.…”
Section: Samplingmentioning
confidence: 99%
“…Additionally, as a result of the interaction between the gut microbiota and the liver ( Deng et al, 2020 ), our findings indicated that seabuckthorn supplementation resulted in an increase in OTU numbers and an FM-biased bacterial community in the SB group compared to the SBM group. Taxonomic changes were observed at the phylum level, as Actinobacteria were found to produce active metabolites against pathogenic microorganisms ( Jami et al, 2015 ), and the current study revealed an increase in Actinobacteria, suggesting a protective role for the SB group.…”
Section: Discussionmentioning
confidence: 70%
“…We used the hindgut tissue from both female and male fish for the omics investigation to prevent sex-biased differences. The complete hindgut contents were collected in sterile tubes and preserved at −80°C for 16S rRNA gene sequencing ( Deng et al, 2020 ). For the sampling of larvae, only the caudal part of 27 dpf larvae has been sampled for HE (Hematoxylin–eosin) staining, during the imaging of the adaptive immune cells.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, whether it can adapt to low temperature directly affects the survival, feeding, and growth of Pearl gentian group. Nevertheless, previous studies mainly focused on feed nutrition and pathology [24][25][26][27] and did not involve research on gene expression related to low temperature. Besides, the molecular regulation mechanism underlying cold stress in pearl gentian grouper species remains largely unidentified.…”
Section: Introductionmentioning
confidence: 99%